Intrauterine Hematoma in the First Trimester and Pregnancy Complications: A Systematic Review and Meta-Analysis - Qin, Zhao-juan; Xu, Yu; Du, Yi; Chen, Ya-li; Sun, Liang; Zheng, Ai (Frontiers in Medicine, 2022)
Background: Studies evaluating the relationship between intrauterine hematoma in the first trimester and prenatal complications are conflicting. Objectives: To evaluate whether intrauterine hematoma identified in the first trimester in women with singleton pregnancies is associated with adverse perinatal outcomes. Search strategy: A comprehensive literature search of three databases (Embase, PubMed, and Web of Science) was performed up to September 2021. Selection criteria: Cohort and case-control studies that have evaluated the relationship between intrauterine hematoma identified before 14 gestational weeks and the risk of prenatal complications, in women with a singleton pregnancy. Data collection and analysis: Two members of our team independently assessed the studies for inclusion, collected the data of interest, and assessed the risk of bias, and calculated pooled odds ratios (ORs) using random-effects models. Main results: Nine studies, including 1132 women with intrauterine hematoma and 11179 controls met the inclusion criteria. Intrauterine hematoma increased the risk of spontaneous abortion (OR 2.15, 95% confidence interval (CI) 1.23-3.75), preterm birth (OR 1.83, 95% CI 1.37-2.43), fetal growth restriction (OR 2.33, 95% CI 1.13-4.83) and placental abruption (OR 3.16, 95% CI 1.23-8.13). No statistically significant association was found between intrauterine hematoma and preeclampsia (OR 1.30, 95% CI 0.87-1.94). Conclusions: Intrauterine hematoma in the first trimester of pregnancy increases the risk of spontaneous abortion, preterm birth, placental abruption, and fetal growth restriction.